MKTG, 13th Edition - Charles W. Lamb; Joe F. Hair; Carl McDaniel (Cengage Learning, 2020)
MKTG from 4LTR Press connects students to the principles of marketing-bringing them to life through timely examples showing how they're applied at the world's top companies every day.